Navigating Life With High‐Grade Glioma: Experiences and Needs of Adolescents and Young Adults - Kaviya Devaraja; Maureen Daniels; Derek S. Tsang; Kim Edelstein; Julie Bennett; Cheryl Kanter; Warren Mason; Abha A. Gupta; Jonathan Avery (Cancer Medicine)
ABSTRACT Background Adolescents and young adults (AYA, 18–39) with high‐grade glioma (HGG) face unique challenges at a life stage focused on autonomy, careers, relationships, and family planning. Aim This study explores their experiences to inform life‐stage appropriate support and resources. Methods In this mixed‐methods study, we surveyed AYA HGG patients at Princess Margaret Cancer Centre (PM) to assess symptom experiences and care satisfaction. Interviews further explored their illness experiences and needs. Descriptive statistics summarized survey data, and thematic analysis guided by Braun and Clarke's framework identified key interview themes. Triangulation compared survey and interview results for a comprehensive understanding. Results Seventeen participants (7 men, 10 women; mean age 30.57) completed surveys and interviews. Triangulation revealed typical AYA challenges, such as delays in education, careers, and relationships, along with HGG‐specific issues. Three main themes emerged: (1) managing cognitive and treatment‐related impacts on life goals, (2) addressing physical and cognitive impairments affecting relationships, and (3) navigating identity loss and independence due to neurological symptoms. Conclusions These findings highlight the need for tailored interventions and educational support integrated into AYA HGG care pathways.